Policy Making and Organizational Decisions in Leadership in Islamic Education Institutions - Yuliyanti, Yuliyanti (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Decision-making by institutional leaders is essentially the act of issuing tactical and operational decisions such as containing the program to be achieved, its implementation strategy and problem-solving strategies, through a decision based on the results of selecting several alternative problems that have been determined for the achievement of madrasa goals. Decision-making must consider various things, think about it carefully. The decisions taken should not only be personal desires and interests or only meet their own needs, but must be far-sighted, the decisions taken are decisions that are the result of data and realities in the institution. This decision must be able to solve existing problems, so that if something happens in the institution that requires resolution, then it can be resolved with alternative decisions and policies. Thus the managerial function of the leader will run as it should, and the success of the institution will be measured from the results of decision making by the leadership, as evidenced by the achievement of the goals set by the institution.